STRATEGI PENGELOLAAN PAJAK DAN TANTANGANNYA DI CV. XYZ BANDUNG - Dini Paryanti; Nurul Ismail Hasan (Jurnal Ekbis (Ekonomi & Bisnis), 2025)
This study aims to analyze the tax management strategies and the challenges faced by CV.XYZ, a micro, small, and medium enterprise (MSME) operating in the religious publishing sector. Using a qualitative descriptive approach, the study explores the company’s tax administration processes through semi-structured interviews, direct observation, and document analysis. The findings indicate that the company has made efforts to fulfill its tax obligations, particularly in terms of formal compliance such as tax return filing and the issuance of tax invoices. However, tax management remains operational in nature and lacks a systematic tax planning framework. The major challenges include unstandardized manual bookkeeping, limited digital literacy, inaccuracies in classifying VAT-related taxable goods, and insufficient staff competence in operating digital tax applications such as e-Faktur and e-Bupot. Furthermore, the company’s material compliance level remains weak due to data inconsistencies and errors in transaction input. The study concludes that the effectiveness of tax management is strongly influenced by bookkeeping quality, human resource competence, and organizational readiness to adopt tax digitalization. Key recommendations include digitalizing financial records, providing continuous tax training, strengthening internal controls, and establishing standardized tax procedures. Keywords: tax management, MSMEs, tax compliance, tax digitalization